Treatment of oligomenorrhea and failure of the corpus luteum. - Onetto, Enrique (2015)
The findings in the experimental use of a new retrosteroide (1-Dihydro-6-Chlor-retroprogesterona) for the treatment of menstrual disorders, constant anovulation or luteal insufficiency in 97 patients were analyzed and compared to observations in 9 patients who received only placebo . This allows us to hold the following suggestions regarding the therapeutic value: 1.-When the endogenous estrogen secretion is adequate and there is no organic lesion disorders are corrected in most patients; 2. is a weak inducer of ovulation. Clomiphene citrate was effective in some patients who premedication with compound retrosteroide had failed; 3. The therapeutic effectiveness in luteal insufficiency is higher, however, a patient in the control group corrected his condition while receiving placebo; 4. The proposed dose not inhibit ovarian function while acting as a progestational agent. It therefore seems particularly useful in the treatment of amenorrhea, irregular excessive bleeding in young patients, yet unwilling to become pregnant; 5. Patients who do not respond to treatment Retroid require careful investigation in search of organic factors; 6. At the doses used Retroid compound has no side effects and does not depress or gonadotropin ovarian function.